An Analysis of Figurative Language in Ariana Grande’s Album “Thank U, Next” - Deni Arnita Hulu; Elia Nova Sembiring; Natalia Widya Pasca Tarigan (Linguistic, English Education and Art (LEEA) Journal, 2021)
This study analyzes the figurative language (simile, metaphor, personification, hyperbole, symbol, irony and idiom) in the song lyrics. This study also aims to determine the most dominant type of figurative language and then to identify the themes of the twelve songs in the song lyrics of Ariana Grande's album "thank u next." This study used descriptive qualitative research. From the results of the analysis, the researcher found that were 73 data using figurative, nine data for simile (12.32%), 17 data for metaphor (23.28%), eight data for personification (10.95%), 10 data for hyperbole (13.69%), nine data for symbols (12.32%), four data for irony (5.47%), and 16 data for idioms (21.91%). The most dominant is a metaphor. The themes contained in each song are Denial for the song Imagine, Needed for the song Needy, Space for the song NASA, Pretend for the song Bloodline and Fake Smile, Rebound Relationship for the song Bad Idea, Relationship for the song Makeup, Brief and Regret for the song Ghost in, Misinterpreted for the song In My Head, Friendship for the song 7 Rings, Empowerment and Self-Love for the song Thank U Next, and Self-Love for the song Break Up With Your Girlfriend, I'm Bored. Keywords: Figurative Language, Song, Theme